Activist Participation in Academic Systems: Three Autoethnographic Case Studies of Academic-activist Positions in Knowledge-work - Engelbert Jensen, Rosa; Emil Mølgaard Thayssen, Albert; Uldbjerg Mortensen, Signe (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
Based on three autoethnographic cases, this article reflects on activist participation in academic systems. The three authors are activists with different attachments to and experiences of academic knowledge-work. Our experiences as activists in academia help us form the argument that many activist contributions to academic systems remain unacknowledged. We are using these overlooked cases to expand existing participatory and activist/action research that often assumes a preliminary distinction between activists and researchers. Instead, we pose critiques of participation that are neither internal (in the sense criticised by Cooke and Kothari) nor external, but formulated from positions in between as activist-academics. Our critiques of academic participation concern exploitation of student work in academic teaching, lack of acknowledgement of activist knowledge in research processes, and tendencies to dismiss activists as professional disseminators of academic knowledge.